Molecular phylogenetics of Crossodactylus Duméril & Bibron, 1841 : (Anura: Hylodidae) - Fabri, Danielle Angelini (2013)
Hylodidae is an anuran family composed of genera Crossodactylus, Hylodes, and Megaelosia, commonly known as torrent frogs , and known to range from northeastern Brazil through southern Paraguay and northern Argentina. Crossodactylus, previously referred to as the most taxonomic problematic of the three, is comprised of 11 small-sized (but for C. grandis) species, currently divided among three species groups: the C. gaudichaudii, C. trachystomus, and C. schmidti groups, the first of which contains the majority of recognized species. The relationship between Hylodidae and other anuran families has been extensively discussed, and hypotheses have been varied. Nonetheless, the monophyly of the group seems well corroborated, and has been recovered in several independent phylogenetic studies. However, despite recurrent mentions to the problematic systematics of Crossodactylus, its phylogenetic relationships remain untested. Furthermore, the only proposed synapomorphy for the group is the absence of the quadratojugal bone, a hypothesis which has already been refuted in literature. In view of the problems still revolving around Crossodactylus, this study aimed to test the monophyly of the genus and its species groups, while clarifying relationships among its species, and among itself and the remainder of hylodid genera. For that, a phylogenetic analysis of 3 mitochondrial and 5 nuclear genes of different degrees of variability was performed on software POY 4.1.2.1 under dynamic homology, employing the maximum parsimony optimality criterion. 72 outgroup taxa, and of 88 ingroup terminals were included. Of the outgroup, 21 taxa comprised of 61 terminals were sequenced by this study. All ingroup sequences were generated in this study, except for those of C. schmidti, for which sequences were already available on GenBank. A total of 14 equally most parsimonious trees of 25,508 steps were found, the conflicts of which were restricted to relationships between terminals of the ingroup. The monophyly of Hylodidae was corroborated once more. Megaelosia was found to be paraphyletic with respect to Hylodes, which is monophyletic. Crossodactylus was recovered as a monophyletic group, sister to the clade comprising the other two hylodid genera. The species groups as currently defined were found not to reflect the actual relationships among species, with the C. gaudichaudii group being paraphyletic with respect to C. schmidti, and likely to C. trachystomus. Also, several species complexes were found within Crossodactylus, and species believed to be widespread were found to be actually several narrowly distributed species. 14 putative species were discovered in addition to the six recognized species sampled. The placement of the five recognized species not sampled by this study remains unknown and, as most of these were last collected in the 1970 1980s, future studies will require morphological evidence in order to address this question.